Terapi Bermain Storytelling dan Literasi Awal untuk Kecemasan Hospitalisasi Anak Prasekolah: Studi Kasus - Caca Tanika; Laili Nur Hidayati; Maili Maghfiroh (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2026)
Background: Hospitalization in preschool children often causes anxiety due to the unfamiliar hospital environment, medical procedures, and reduced opportunities for play. Unresolved anxiety may interfere with treatment and recovery. Storytelling play therapy combined with early literacy activities is a developmentally appropriate non-pharmacological intervention for reducing hospitalization anxiety. However, evidence regarding the implementation of this combined intervention in hospitalized preschool children remains limited. Objective: To describe the potential effect of storytelling play therapy combined with early literacy activities on reducing hospitalization anxiety in a preschool child through a case study. Case report: A 3-year-old boy was admitted with bronchopneumonia in stable clinical condition experienced hospitalization anxiety, with an initial Face Image Scale (FIS) score of 4. The nursing diagnosis was anxiety related to a situational crisis (hospitalization). A single 45-minute session of storytelling play therapy integrated with early literacy activities was conducted using an age-appropriate animal-themed picture book, with parental involvement. The storytelling was delivered using engaging intonation and facial expressions while encouraging the child to identify pictures, vowels, and simple consonants embedded in the story. Anxiety levels were assessed before and after the intervention using the FIS. Results: Following the intervention, the child's FIS score decreased from 4 to 1. The patient appeared calmer, more cooperative, and interacted more positively with healthcare professionals during hospitalization. Conclusion: In this case study, storytelling play therapy combined with early literacy activities was associated with a reduction in hospitalization anxiety in a preschool child.INTISARILatar belakang: Hospitalisasi pada anak prasekolah sering menimbulkan kecemasan akibat lingkungan rumah sakit yang tidak familiar, prosedur medis, serta berkurangnya kesempatan bermain. Kecemasan yang tidak teratasi dapat mengganggu proses perawatan dan pemulihan anak. Terapi bermain storytelling dan literasi awal merupakan intervensi nonfarmakologis yang sesuai dengan tahap perkembangan anak untuk membantu mengurangi kecemasan hospitalisasi. Namun, bukti studi kasus mengenai penerapan kombinasi intervensi tersebut pada anak prasekolah yang menjalani hospitalisasi masih terbatas. Tujuan: Mendeskripsikan pengaruh terapi bermain storytelling dan literasi awal dalam menurunkan kecemasan hospitalisasi pada anak prasekolah dalam studi kasus. Laporan kasus: Seorang anak laki-laki berusia 3 tahun dengan diagnosis bronkopneumonia pada hari pertama perawatan berada dalam kondisi klinis stabil, tetapi mengalami kecemasan hospitalisasi dengan skor awal Face Image Scale (FIS) sebesar 4. Masalah keperawatan yang ditegakkan adalah kecemasan berhubungan dengan krisis situasional (hospitalisasi). Intervensi terapi bermain storytelling yang dipadukan dengan aktivitas literasi awal diberikan dalam satu sesi selama ±45 menit menggunakan buku cerita bergambar bertema hewan yang sesuai dengan usia anak, dengan pendampingan orang tua. Storytelling dilakukan menggunakan intonasi dan ekspresi yang menarik serta melibatkan anak dalam mengenali gambar, huruf vokal, dan huruf konsonan sederhana yang terintegrasi dalam alur cerita. Tingkat kecemasan dievaluasi sebelum dan sesudah intervensi menggunakan FIS. Hasil: Setelah intervensi, skor FIS menurun dari 4 menjadi 1. Pasien tampak menjadi lebih tenang, kooperatif, serta berinteraksi lebih baik dengan tenaga kesehatan selama perawatan. Simpulan: Terapi bermain storytelling dan literasi awal pada studi kasus ini berpengaruh terhadap penurunan kecemasan hospitalisasi pada anak prasekolah.